PRELIMINARY REVISIONS OF SOME GENERA OF MALAYSIAN IPILIONACEAE V - A CENSUS OF THE GENUS DESMODIUM - m. s. knaap; van Meeuwen (Reinwardtia, 1962)
The generic circumscription accepted is in a rather wide sense, including the synonyms Phyllodium,Dicerma, Aphyllodium,Meibomia, Monar-throcarpus, Pteroloma, Coda/riocalyx, etc.The generic delimitation against Alysicarpus seems doubtful; see the discussion under 2. Desmodium alysicarpoides.In all 39 species have been recognized among which none is newly recorded for the Malaysian area. Another, 4-0. D. bolsteri Merr., of which no material was available, could not be clarified. Of Ul- D. uncinatum (Jacq.)DC, an American introduction, I had no material either.A number of specific names have been reduced: D. muelleri Bth. and D. neurocarpum Bth. to D. filiforme Zoll., which is not endemic in Malaysia and appears to be a species which finds its widest distribution in North Australia and Queensland; D. archboldianum Baker f. from New Guinea is reduced to D. nemorosum F. v. M.; D. cumingianum (Bth.) Bth. from the Philippines is merged with D. umbellatum (L.) DC; D. podocarpum DC. and D. fallax Schindl. cannot be separated from D. racemosum (Thunb.) DC; D. capitatum (Burm. f.) DC. is reduced to D. styracifolium (Osb.) Merr.; D, longibracteatum Schindl., D. rufihirsutum Craib, and D. virga-tum Zoll. are both merged with D. velutinum (Willd.) DC; Dicerma novo-guineense Schindl. and Dicerma hispidum Schindl. have both been reduced to D. biarticulatum (L.) F. v. M. Besides, two varieties in D. nemorosum and D. adscendens cannot be upheld.Two new names are proposed, viz D. alysicarpoides for D. parviflorum (Dalz.) Baker 1876, non Mart. Galeotti, 1843, and D. blandum for D. ele-ns (Lour.)Bth. 1861, non DC. 1825 nee Schlecht. 1838.Two new varietal combinations are D. biarticulatum var. australiense (Schindl.) van Meeuwen and D. velutinum var. longibracteatum (Schindl.) van Meeuwen.A key to and synonymy and distribution of the species has been given. Indexes to collections and to names are provided at the end.